Perception-based methods and beyond: a current opinion on how to assess static stretching intensity - Warneke, K.; Blazevich, A. J.; Jochum, D.; Behm, D. G.; Thomas, E.; Nakamura, M.; Afonso, J. (Sports Medicine, 2025)
Muscle stretching is widely used in clinical, athletic, and otherwise healthy populations, yet a consensual definition of stretch intensity—a key component of stretch load—does not exist. This is important because the effects of stretch intensity on range of motion and strength are controversial but suggested to affect clinical practice and scientific research. Most commonly, stretch intensity is defined in relation to an individual`s perceived level of discomfort or pain; however, these definitions are problematic for several reasons, including that consensual and objective quantifiable definitions of `pain` and `discomfort` do not exist, perceptions vary widely (and may not be sensed in some populations), and their ordinal (interval) nature is problematic from a statistical (research) point of view. The maximal range of motion or stretch distance may instead be useful; however, it can be difficult to define the `start of stretch` and tissue stress varies non-linearly with range of motion or distance, meaning tissue load (stress) varies markedly with small changes in joint angle or distance near the stretch limit but varies less when stretches are performed further from it. Alternatively, setting joint angles or stretch distances as a percentage of the peak passive torque or resistive force can circumvent these issues, removing the need to define the `start of stretch` and ensuring that intensity changes largely reflect changes in tissue load; however, torque/force measurement can sometimes be difficult or impossible to assess. A concerted research effort is thus required to produce an accepted definition of stretch intensity, and then to clarify how this can be quantified in scientific and practical settings.